Pengaruh Pupuk Organik Cair Kotoran Kambing dan Limbah Kulit Nanas terhadap Pertumbuhan Tanaman Kailan (Brassica oleracea L. Alboglabra) - Anisa Novita; Evie Palenewen; Vandalita M. Rambitan; Herliani Herliani; Zenia Lutfi Kurniawati (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This research uses waste that is currently quite abundant with waste management that has not been optimised so that it can result in environmental pollution, therefore this research uses animal waste, namely goat manure with household waste, namely pineapple peel as organic fertiliser. The purpose of this study was to determine the effect of liquid organic fertiliser goat manure with pineapple peel waste, as well as to determine and assess the optimal dose for the growth of kailan plants. This type of research uses a group randomised design method with 5 treatments, namely KN0 (control), KN1 (15%) KN2 (30%), KN3 (45%), KN4 (60%). The parameters used are plant height (cm), number of leaves (strands), and wet weight (grams) of plants. The results of the observation of Fhitung treatment of plant height in a row of 65.91 (10 HST), 106.42 (20 HST), 205.75 (30 HST) > Ftable 0.05 (3.12), the results of Fhitung number of leaves in a row of 45.22 (10 HST), 22.48 (20 HST), 40.37 (30 HST) > Ftable 0.05 (3.12), and the results of Fhitung wet weight with a value of 119.90 > Ftable 0.05 (3.12). Based on data analysis, there is an effect of liquid organic fertiliser goat manure and pineapple peel on the growth of kailan plants (Brassica oleracea L. Alboglabra) with a significant concentration of 30%.